Antarctic krill lipid extracted by subcritical n-butane and comparison with supercritical CO2 and conventional solvent extraction. (August 2018) - Sun, Dewei; Cao, Chen; Li, Bo; Chen, Hongjian; Li, Jinwei; Cao, Peirang; Liu, Yuanfa
Abstract: Antarctic krill lipid has unique biological efficacy, however, the efficient and eco-friendly extraction of its lipid remains a challenge. In this study, Antarctic krill lipid extraction conditions using subcritical n- butane were investigated and optimized by response surface methodology. The optimal extraction conditions using subcritical n- butane were, 120 min dynamic extractions at 40 °C and 1.0 MPa. Lipids extracted by the subcritical n- butane were further compared with those extracted by supercritical CO2 and traditional solvents. Results indicated that the lipid extraction by using subcritical n -butane had a higher lipid recovery rate (81.2 ± 1.5%), higher astaxanthin content (248.4 ± 5.2 mg/kg) and the highest tocopherol content (67.7 ± 3.2 mg/kg). Furthermore, the lipids' volatile components and flavor components were further investigated. Results revealed that the lipid extracted by subcritical n -butane had lower 1-Penten-3-ol and aldehydes content, indicating less lipid oxidation and higher sulfur-containing compounds which might contribute to the overall aroma of Antarctic krill lipid. Additionally, Antarctic krill lipid extracted by subcritical n -butane had a higher lipid recovery rate and better nutritional quality. Thus, subcritical n -butane could be the best solvent for efficiently extract Antarctic krill lipid. Highlights: Optimal extraction conditions were extraction 120 min under 40 °C and 1.0 MPa. The lipid extracted by subcritical had a more bioactive substances. The lipid extracted by subcritical had less oxidation.